2014
DOI: 10.1002/smj.2264
|View full text |Cite
|
Sign up to set email alerts
|

Examining a key corporate role: The influence of capital allocation competency on business unit performance

Abstract: Research on the role of the corporate office in firm performance has focused on establishing how much performance variance can be attributed to a "corporate effect," with little attention devoted to understanding how this influence occurs. In this study, we model capital allocation competency as a dynamic managerial capability and find that lower levels of allocation competency in the form of excess investment to business units with relatively poorer future prospects reduce business unit performance. We also f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(127 citation statements)
references
References 67 publications
4
123
0
Order By: Relevance
“…The estimated corporate effect ranges from 4% (McGahan & Porter, 1997), to 2.7% for a "stable corporate effect" plus 4.6% for specific corporate management decisions (Adner & Helfat, 2003), to somewhere between 8.6% and 12% (McGahan & Porter, 2002). While these studies have primarily attributed this effect to the firm's diversification strategy, scholars have recently pointed out that these corporate effects can also stem from other aspects of corporate strategy and structure, including the CHQ's design and roles (Adner & Helfat, 2003;Arrfelt, Wiseman, McNamara, & Hult, 2014). Therefore, studies that distill the corporate effect into components will contribute to our understanding of the CHQ's impact and offer a more accurate picture of the corporate strategy's impact.…”
Section: The Chq's Raison D'êtrementioning
confidence: 99%
“…The estimated corporate effect ranges from 4% (McGahan & Porter, 1997), to 2.7% for a "stable corporate effect" plus 4.6% for specific corporate management decisions (Adner & Helfat, 2003), to somewhere between 8.6% and 12% (McGahan & Porter, 2002). While these studies have primarily attributed this effect to the firm's diversification strategy, scholars have recently pointed out that these corporate effects can also stem from other aspects of corporate strategy and structure, including the CHQ's design and roles (Adner & Helfat, 2003;Arrfelt, Wiseman, McNamara, & Hult, 2014). Therefore, studies that distill the corporate effect into components will contribute to our understanding of the CHQ's impact and offer a more accurate picture of the corporate strategy's impact.…”
Section: The Chq's Raison D'êtrementioning
confidence: 99%
“…This research has shown the challenges of efficient capital allocation to be numerous, ranging from agency problems (Scharfstein andStein 2000, Rajan et al 2000) to cognitive distortions (Christensen and Bower 1996, Sull 1999, Gilbert 2001) and even to inefficient comparisons relative to aspiration levels (Arrfelt et al 2013, Arrfelt et al 2015. This study takes these ideas a step further by introducing the possibility that the limit to managerial attention is an additional constraint that could (and appears to) prevent the managers of multi-business firms from allocating capital in an efficient manner to all of the businesses operating in these companies.…”
Section: Discussionmentioning
confidence: 99%
“…Field research built upon this insight by showing that managers' failure to respond appropriately to the threat of new technologies due to their cognitive biases limits their abilities to allocate capital efficiently within the multi-business firms they run (Christensen and Bower 1996, Sull 1999, Gilbert 2001. Even more recently, studies have productively taken steps towards more precisely unpacking the contingencies in which managers make efficient versus inefficient capital allocation decisions (Khanna andTice 2001, Maksimovic andPhillips 2002), particularly by developing new frameworks that analyze how the tradeoff between growth and profitability influences these decisions (Bardolet et al 2010, Vierreger 2012 and by introducing the ideas of historical and social aspiration levels and how they might affect capital allocation decision-making (Arrfelt et al 2013, Arrfelt et al 2015.…”
Section: Capital Allocation In Diversified Firmsmentioning
confidence: 99%
See 2 more Smart Citations